Liquidity Measurement Problems in Fast, Competitive Markets: Expensive and Cheap Solutions - HOLDEN, CRAIG W.; JACOBSEN, STACEY (Journal of Finance, 2014)
ABSTRACT Do fast, competitive markets yield liquidity measurement problems when using the popular Monthly Trade and Quote (MTAQ) database? Yes. MTAQ yields distorted measures of spreads, trade location, and price impact compared with the expensive Daily Trade and Quote (DTAQ) database. These problems are driven by (1) withdrawn quotes, (2) second (versus millisecond) time stamps, and (3) other causes, including canceled quotes. The expensive solution, using DTAQ, is first‐best. For financially constrained researchers, the cheap solution—using MTAQ with our new Interpolated Time technique, adjusting for withdrawn quotes, and deleting economically nonsensical states—is second‐best. These solutions change research inferences.